Women’s experience of intimate partner sexual violence in southwest, Nigeria - Awolaran, Olusegun; Awolaran, Dorcas B.; Olabode, Aderemi Temitayo (International Journal Of Community Medicine And Public Health, 2025)
Background: Intimate partner sexual violence (IPSV) is more prevalent than many people realize because it is largely under-reported due to associated stigma, silence and social norms. Traditional African setting tends to condone male sexual entitlement and minimize women's bodily autonomy, hence conditioning women to accept IPSV. Methods: A mixed-methods study was conducted to assess the prevalence of IPSV and factors associated with IPSV in selected rural communities of Oyo State, Nigeria. A total of 677 women completed the quantitative interview, while twelve IDIs and nine FGDs were also conducted. Results: The findings from this cross-sectional study showed that 9% of respondents in this study experienced sexual violence from their partners in the 12 months preceding the survey and 65.6% of respondents had attitudes that supported sexual violence. Women who have been married for between 6 to 10 years (AOR=0.44; 95% CI 0.19-0.99) and were from households in the richer wealth tertile (AOR=0.31; 95% CI 0.15-0.65) were significantly less likely to experience IPSV compared to their contemporaries. On the other hand, respondents whose attitudes were supportive of IPSV (AOR=4.04; 95% CI 1.17-13.94) and physical IPV (AOR=2.99; 95% CI 1.49-6.00) were significantly more likely to experience IPSV compared to their counterparts. Conclusions: Intimate partner sexual violence is common in southwest, Nigeria and there are attitudes and beliefs that underpin this behavior, which need to be addressed. Addressing the individual and societal attitudes can improve prevention strategies for IPSV in Nigeria.